2021
DOI: 10.3390/ijms22168782
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Mechanosensitive Ion Channels and Calcium Regulatory Proteins in Cardiovascular Health and Disease

Abstract: Mechanosensitive ion channels are widely expressed in the cardiovascular system. They translate mechanical forces including shear stress and stretch into biological signals. The most prominent biological signal through which the cardiovascular physiological activity is initiated or maintained are intracellular calcium ions (Ca2+). Growing evidence show that the Ca2+ entry mediated by mechanosensitive ion channels is also precisely regulated by a variety of key proteins which are distributed in the cell membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 157 publications
0
21
0
Order By: Relevance
“…In the cardiovascular system, myocardial contraction pumps blood into the arteries, and blood flow creates friction and pressure on the blood vessels ( 49 ). MSCs are widely expressed in the cardiovascular system, sensing changes in mechanical forces and transducing mechanical signals into chemical and electrical signals ( 50 ). Piezo1 is one of the cardiovascular sense and plays a crucial role in cardiovascular development, blood pressure regulation, hypertensive vascular remodeling, and other physiology and pathology ( 51 54 ).…”
Section: Piezo1 Channel-mediated Chronic Inflammationmentioning
confidence: 99%
“…In the cardiovascular system, myocardial contraction pumps blood into the arteries, and blood flow creates friction and pressure on the blood vessels ( 49 ). MSCs are widely expressed in the cardiovascular system, sensing changes in mechanical forces and transducing mechanical signals into chemical and electrical signals ( 50 ). Piezo1 is one of the cardiovascular sense and plays a crucial role in cardiovascular development, blood pressure regulation, hypertensive vascular remodeling, and other physiology and pathology ( 51 54 ).…”
Section: Piezo1 Channel-mediated Chronic Inflammationmentioning
confidence: 99%
“…Aside from this, some scientific reports recently indicated that Ca 2+ entry mediated by mechanosensitive channels is regulated by a diversity of major proteins which are located in the cellular membrane or endoplasmic reticulum. It was shown that mechanosensitive channels can be physically connected with some Ca 2+ regulatory proteins [ 49 ]. For example, Piezo and SERCA were discovered to cross-talk to each other through physical interaction in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma membrane Ca 2+ ATPase (PMCA) expels Ca 2+ outside the cell [ 83 ]. The sarco-endoplasmic reticulum Ca 2+ ATPase (SERCA) displaces Ca 2+ into internal stores [ 84 , 85 ]. These stores are remnants given to platelets from the endoplasmic/sarcoplasmic reticulum (ER/SR) of megakaryocytes [ 86 , 87 ] known as the dense tubular system (DTS) [ 88 ].…”
Section: Cytosolic Ion Fluxes In Procoagulant Coat Plateletsmentioning
confidence: 99%